2018
DOI: 10.1159/000496043
|View full text |Cite
|
Sign up to set email alerts
|

Building a Competing Endogenous RNA Network to Find Potential Long Non-Coding RNA Biomarkers for Pheochromocytoma

Abstract: Background/Aims: Accumulating evidence has shown that long non-coding RNAs (lncRNAs) in competing endogenous RNA (ceRNA) networks play crucial roles in tumor survival and patient prognosis; however, studies investigating ceRNA networks in pheochromocytoma (PCC) are lacking. In this study, we investigated the pathogenesis of PCC and whether lncRNAs acting through ceRNAs networks were associated with prognosis. Methods: A total of 183 PCC samples and 3 control samples from The Cancer Genome Atlas database were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…The lincRNAs with differential expression signature in PCPG compared to normal adrenal medulla matches with a previous study performing the same analysis from TCGA data (e.g. MIAT , BSN‐AS2 ).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The lincRNAs with differential expression signature in PCPG compared to normal adrenal medulla matches with a previous study performing the same analysis from TCGA data (e.g. MIAT , BSN‐AS2 ).…”
Section: Discussionsupporting
confidence: 85%
“…We also compared the expression of lincRNAs in PCPGs vs . normal adrenal medulla from TCGA (similar to Liang et al …”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…In our research, lncRNA BSN-AS2 was found to aberrantly highly express in spinal OS tissues compared with adjacent normal tissues. Besides, BSN-AS2 differentially expressed in pheochromocytoma (PCC) samples and was recognized as an independent prognostic biomarker and potential therapeutic target for PCC [19]. Nevertheless, the underlying role and function of lncRNA BSN-AS2 in spinal OS was largely unknown.…”
Section: Introductionmentioning
confidence: 99%